Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen pada PT Jafar Plaza Bangunan Tukka Aek Tolang Pandan Tapanuli Tengah - Rifqah Annisah; Shafwan Koto; Jeniusman A. Hutagalung (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of product quality and service quality on consumer satisfaction at PT Jafar Plaza Bangunan Tukka Aek Tolang Pandan Central Tapanuli. The type of research used in this study is a quantitative research method. The sample in this study was consumers at PT Jafar Plaza Bangunan with a questionnaire distribution of 72 respondents. Based on the results of the t-test in the study, it is known that the t-value of product quality is 4.672 and service quality is 3.378> t table of 1, 667, it can be concluded that product quality and service quality partially or individually have an effect on consumer satisfaction at PT Jafar Plaza Bangunan Tukka Aek Tolang Pandan Central Tapanuli